Pendampingan Entrepreneurship Budidaya dan Pemasaran Ikan Cupang (Betta sp.) oleh Alumni Jurusan Akuakultur, Universitas Bangka Belitung - Kurniawan, Andri (LPPM UNIVERSITAS DIAN NUSWANTORO, 2021)
Entrepreneurship assistance to alumnus's business ideas is a practice that cannot be separated from the obligations and devotion of a lecturer as a form of dedication to the independence and existence of alumnus in society. This service activity aimed to provide assistance to alumni of the Aquaculture Department, Bangka Belitung University in pioneering and building a betta fish (Betta sp.) cultivation and marketing business. This activity was carried out through the stages of introducing the potential for ornamental fish cultivation, building relationships with ornamental fish cultivators and marketers, and formulating promotional strategies in starting businesses, marketing, and developing alumni businesses. This mentoring activity resulted in a pilot business for ornamental fish cultivation and marketing, especially for betta fish, namely the Exotic Betta. The business that was initiated within three months has shown business prospects with an increase in sales and expansion of the marketing area, both in Pangkalpinang City and regencies in Bangka Island to areas outside Bangka Island. The promotion and marketing of the Exotic Betta betta fish through online media and social media has made this business unit quickly recognized by betta fish hobbyists. Business development needs to be done by diversifying commodities to increase and develop marketing business for ornamental fish.